(untitled) (Academicia Globe: Inderscience Research, 2022)
The prevalence of social deficiency and vitamin D deficiency in various parasitic diseases today is one of the most important theoretical and practical problems of medicine due to the level of morbidity among patients of different ages around the world, the complications that it causes, the medical, social, economic damage that it brings. The widespread prevalence of vitamin D and calcium deficiency worldwide, in terms of increasing the pathogenesis of the disease, damage to many organs and systems, indicates a revision of this problem, scientific interest in conducting research in this area. Vitamin D and calcium deficiency has been found to have a negative effect on the immune system of bales. Vitamin D and calcium deficiency has been found to have a negative effect on the immune system of bales. According to Australian scientists, 94% of children in countries located in northern latitudes suffer from hypocalcemia, 86% of them suffer from rickets.